Radiometric Survey in Mammography: Review of regulations, recommendations, field and laboratories practices and first tests. (Brazilian Journal of Radiation Sciences (BJRS), 2019)
A review about Radiometric Survey in Mammography (RSM) in terms of regulatory documents, recommendations, radiation meters, besides field and laboratories practices shows that there is not many specific information about how these radiation area monitoring tests shall be performed. A search on the website of the most known manufacturers of radiation meters was made, but only one fully comply the requirements for RSM application. Tests with four laboratorial reference chambers, but none specific to RSM, were made submitting them to ISO N 20, 25 and 30 calibration setup (Based on document ISO 4037-1:1996) and their behavior in terms of HVL’s and air kerma rate measurements was compared to endorse some evaluations. The result of this work suggests that some RSM performed in Brazil, with nonspecific chambers and calibration can have underestimation of until 60% in those measurements, once a lack of specific information and specific calibration services in this country contributes for this scenario.